Design and verification of a 25 K multiple-SNP liquid-capture chip by target sequencing for dairy goat - Jianqing Zhao; Yaling Wang; Jiayidaer Kamalibieke; Ping Gong; Fuhong Zhang; Huaiping Shi; Wei Wang; Jun Luo (BMC Genomics)
Abstract Background In the genetic breeding research of dairy goats, traditional genotyping methods have limitations, and existing goat chips have shortcomings in functional loci and other aspects, which cannot meet the precise genetic analysis needs of dairy goats. Genotyping by Target Sequencing (GBTS) in the new generation of sequencing technology provides the possibility to solve these problems. Results A large number of candidate SNP sites related to important economic traits in dairy goats were identified through various analysis and screening methods. The chip ultimately retained 27,396 SNP sites for probe design, which can detect 46,459 SNPs. The site distribution is uniform, and the sequencing data efficiency, base quality, alignment rate, and other indicators are good. The chip SNP detection rate is high and the heterozygosity of gene typing is reasonable. GWAS was performed on 200 dairy goats for litter size and birth weight traits, and multiple genome-wide significantly related SNPs and related genes (litter size trait: SCAP, PTPN23, KIF9, ANTXRL, and GRID1. birth weight trait: NALCN, LRRN2, TMEM132D, COL5A2, and HS3ST1) were detected. Conclusion The 25 K multiplex SNP liquid phase capture chip designed in this study has excellent performance and is of great value for genetic research and breeding of dairy goats, providing strong support for the development of the dairy goat industry.